Aplikasi Pembelajaran Mata Pelajaran Bahasa Inggris Untuk Anak Tunagrahita - Syahril, Hilman; Rahayu, Sri; Ramadhani, Reski (Jurnal Algoritma, 2025)
Rapid technological developments have changed the learning paradigm where learning media technology becomes one of the effective tools in the learning process. Learning media not only motivates students, but also provides wider access to education, including for students with special needs such as intellectual disabilities. However, English learning media technology, especially for students with special needs, is still limited. Therefore, this study is to build English learning media for mild intellectual disabilities, to make learning easier and more enjoyable anywhere and anytime. The methodology used is the Multimedia Development Life Cycle consisting of several stages, namely Concept, Design, Material Collecting, Assembly, Testing, Distribution to build an application to visualize English material according to the 2013 curriculum for mild intellectual disabilities. The application is targeted for Junior High School (SMP) students. Alpha and beta testing was carried out, at the alpha testing stage, a functional application test was carried out where each menu was tested where all menu functions ran successfully. For beta testing, testing was carried out to identify user satisfaction with the application using the End User Computing Satisfaction method, the sampling method used a saturated sample approach. The results of the overall percentage of user satisfaction from the five dimensions in the EUCS method obtained results with very satisfied criteria with an average of all dimensions of 95.4% with the Android-based English subject learning media application for mentally retarded children.